2012
DOI: 10.1557/jmr.2012.170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of amorphous zinc tin oxide semiconductors

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…5 In perovskite ZnSnO 3 crystals, each Zn and Sn octahedrons share corners with another Zn and Sn octahedron structure 2 and during crystallization through solid-state reactions, transforms from its metastable form to thermodynamically stable zinc orthostannate phase, typically reported to occur at temperatures above 500°C. 3 The inverse spinel structure of Zn 2 SnO 4 consist of a Zn atom that is centered at alternating tetrahedral of ZnO 4 with four nearest-neighbor oxygen (O) atoms, while equal numbers of Zn and Sn atoms located at the center of octahedral ZnO 6 or SnO 6 with six nearest-neighbors O atoms in the lattice. 6 Because of their superior electrical conductivity and high visible light transparency, 7 ZTO is also considered as a potential semiconductor material for solar cells, [8][9][10] photocatalysis, 11,12 gas sensors, [13][14][15] electrode material for Li-ion batteries 16 , and transparent conducting substrates 17 etc.…”
mentioning
confidence: 99%
“…5 In perovskite ZnSnO 3 crystals, each Zn and Sn octahedrons share corners with another Zn and Sn octahedron structure 2 and during crystallization through solid-state reactions, transforms from its metastable form to thermodynamically stable zinc orthostannate phase, typically reported to occur at temperatures above 500°C. 3 The inverse spinel structure of Zn 2 SnO 4 consist of a Zn atom that is centered at alternating tetrahedral of ZnO 4 with four nearest-neighbor oxygen (O) atoms, while equal numbers of Zn and Sn atoms located at the center of octahedral ZnO 6 or SnO 6 with six nearest-neighbors O atoms in the lattice. 6 Because of their superior electrical conductivity and high visible light transparency, 7 ZTO is also considered as a potential semiconductor material for solar cells, [8][9][10] photocatalysis, 11,12 gas sensors, [13][14][15] electrode material for Li-ion batteries 16 , and transparent conducting substrates 17 etc.…”
mentioning
confidence: 99%
“…This is consistent with previously reported ZTO TFTs with an atomic ratio of zinc:tin of either 2:1 or 1:1 by rf magnetron sputtering. 20,30,54 In our work, ZTO TFTs (50% Sn) which have an actual tin content of 63% can no longer be turned off, while ZTO Fig. 7(b)).…”
Section: à2mentioning
confidence: 74%
“…2016) deposited by rf magnetron sputtering from ceramic targets but is less pronounced (up to a factor of 1.3). 6,7,11,54 Preferential sputtering is a common phenomenon whenever a target containing two or more elements is subjected to a particle impact, and it arises from the differences in mass, chemical binding and bombardment-induced Gibbsian segregation which are in turn related to the sputtering yield. 55 Using 500 eV Ar þ ion as the sputtering gas, the sputtering yield of elemental tin and zinc are estimated to be 1.56 and 4.6, respectively.…”
Section: -4mentioning
confidence: 99%
“…Zn-Sn-O (ZTO) is a low-cost indium-free alternative transparent amorphous oxide semiconductor with excellent electrical properties for TFT applications. 3,12,13 Recently we have demonstrated bipolar resistive switching in solution-deposited ZTO memrsitors and found that the resistive switching was consistent with a combined filamentary/interfacial mechanism. 14 However, to better understand the switching mechanism for ZTO memristors we have fabricated devices using RF sputter-deposited ZTO in this study.…”
Section: Introductionmentioning
confidence: 85%